2023
DOI: 10.1021/acs.joc.2c02653
|View full text |Cite
|
Sign up to set email alerts
|

Stereodivergent Desymmetrization of Phenols En Route to Modular Access to Densely Functionalized Quinazoline and Oxazine Scaffolds

Abstract: The de novo assembly of stereochemically and skeletally diverse scaffolds is a powerful tool for the discovery of novel chemotypes. Hence, the development of modular, step- and atom-economic synthetic methods to access stereochemically and skeletally diverse compound collection is particularly important. Herein, we show a metal-free, stereodivergent build/couple/pair strategy that allows access to a unique collection of benzo[5,6][1,4]oxazino[4,3-a]quinazoline, quinolino[1,2-a]quinazoline and benzo[b]benzo [4,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
(70 reference statements)
0
1
0
Order By: Relevance
“…In contrast to the racemic condensation of ortho -diaminobenzene with dialdehyde/formyl-tethered cyclohexadienone under the influence of formic acid/TFA, currently, there remains a lack of comprehensive reports detailing the organocatalytic synthesis of enantioenriched fused benzimidazoles through amination/aza-Michael addition reactions (Scheme Ac) . Reviewing relevant literature on such a methodology, we found that the Liqin Qiu group documented a chiral phosphoric acid-catalyzed cascade reaction in 2014, where the cascade sequence involves imine formation–nucleophilic addition followed by lactamization (Scheme B)…”
mentioning
confidence: 99%
“…In contrast to the racemic condensation of ortho -diaminobenzene with dialdehyde/formyl-tethered cyclohexadienone under the influence of formic acid/TFA, currently, there remains a lack of comprehensive reports detailing the organocatalytic synthesis of enantioenriched fused benzimidazoles through amination/aza-Michael addition reactions (Scheme Ac) . Reviewing relevant literature on such a methodology, we found that the Liqin Qiu group documented a chiral phosphoric acid-catalyzed cascade reaction in 2014, where the cascade sequence involves imine formation–nucleophilic addition followed by lactamization (Scheme B)…”
mentioning
confidence: 99%